A Vibrational Spectroscopy Study on Anserine and Its Aqueous Solutions - Akkaya, Yasemin; Balcı, Kubilay; Gören, Yeliz; Stricker, Moogega C.; Ritzhaupt, G.; Stover, D. D.; Collier, W. B.; AKYÜZ, SEVİM (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2015)
In this study based on vibrational spectroscopic measurements and Density Functional Theory (OFF), we aimed for a reliable interpretation of the IR and Raman spectra recorded for anserine in the solid phase and water (H2O) and heavy water (D2O) solutions. Initial DFT calculations at the B3LYP/6-31G(d) searched possible conformers of the anserine zwitterion using a systematic conformational search. The corresponding equilibrium geometrical parameters and vibrational spectral data were determined for each of the stable conformers (in water) by the geometry optimization and hessian calculations performed at the same level of theory using the polarized continuum model (PCM). The same calculations were repeated to determine the most energetically preferred dimer structure for the molecule and the associated geometry, force field and vibrational spectral data. The harmonic force constants obtained from these calculations were scaled by the Scaled Quantum Mechanical Force Field (SQM) method and then used in the calculation of the refined wavenumbers, potential energy distributions, IR and Raman intensities. These refined theoretical data, which confirm the zwitterion structure for anserine in the solid phase or aqueous solvents, revealed the remarkable effects of intermolecular hydrogen bonding on the structural properties and observed IR and Raman spectra of this molecule. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anserine; Vibrational Spectra; Hydrogen Bonding; SQM; Scaled Wavenumbers; Ab Initio; Raman Spectra; Force Fields; L-Histidine; Molecular Geometries; Carnosine; Density; Ir; Dipeptides; Complexes